Competing with the Big Boys - Strategies for Growth for a Startup Company in the Singapore Food Industry - Chew, Kee Heng (2010)
Entrepreneurship provides the basis for satisfying of personal goals and possibly profit maximization; Singapore has a good infrastructure in place to facilitate new business setup and other business functions. Being one of the first few industries that have promoted trade and main revenue drivers, the Singapore Food Industry is in its mature state and entrenched with established big-name global, regional and national players with long histories. But because of its ability to innovate, and with consumers constantly looking for new refreshing tastes, the Food industry continues to be earmarked by the government as the few pillars of growth and therefore has an abundance of opportunities for the entrepreneurially adventurous and hungry (Tan 2002).